Astragaloside IV supplementation attenuates cognitive impairment by inhibiting neuroinflammation and oxidative stress in type 2 diabetic mice - Zhang, Yaxuan; Yuan, Yuan; Zhang, Jiawei; Zhao, Yao; Zhang, Yueqi; Fu, Jianliang (Frontiers in Aging Neuroscience, 2022)
Diabetic cognitive impairment is one of the most common complications of type 2 diabetes mellitus (T2DM), whereas optimized therapeutic strategies are not available yet. Astragalosides IV (AS-IV) is a Traditional Chinese Medicine presenting diverse pharmacological properties including anti-inflammatory and antioxidant effects. However, the effects of AS-IV on diabetes-related cognitive impairment and its precise mechanisms remain largely unknown. T2DM mice, induced by high fat diet (HFD) and intraperitoneal injection of low-dose streptozotocin (STZ) were administrated with AS-IV every other day for 8 consecutive weeks. Learning and memory abilities were assessed subsequently using Y maze test and anxious behavior was evaluated using open field test. Then, morphology and number of neurons and microglia were observed by HE staining or immunohistochemistry. Oxidative stress biomarkers and pro-inflammatory cytokines were determined using relevant kits. In addition, the expression levels of Nrf2, Keap1, HO-1, and NQO1 were determined by western blot analyses. The results indicated that AS-IV administration significantly improved neuronal damage and cognitive deficit in T2DM mice. Meanwhile, oxidative stress and neuroinflammation were also ameliorated in T2DM mice, which might be attributed to the regulation of Nrf2/Keap1/HO-1/NQO1 pathway in T2DM mice. Taken together, these data suggest that AS-IV ameliorates cognitive impairment in T2DM mice by attenuating oxidative stress and neuroinflammation, possibly through modulating Nrf2/Keap1/HO1/NQO1 pathway.